Providing Effective Library Services for Research. - Webb, Jo (Facet Publishing, 2013)
Researchers rely on libraries to provide the information they need; equally, supporting research is a fundamental reason for libraries' existence. This book explores the relationship between libraries and researchers, focusing on developing and managing effective library services to support research.